A Mini-ISY100 Transposon Delivery System Effective in γ Proteobacteria - Conte, Emanuele; Mende, Linda; Grainge, Ian; Colloms, Sean D. (Frontiers in Microbiology, 2019)
Transposons are invaluable biological tools for the genetic manipulation of microorganisms. ISY100 from Synechocystis sp. PCC6803 is a member of the Tc1/mariner/IS630 superfamily, and is characterized by high transposition efficiency and a strong preference for TA target sequences. In this paper, we describe the design and application of a miniISY100 suicide vector for the in vivo creation of stable random transposon insertion libraries. The system was successfully applied in seven species belonging to four different orders of γ proteobacteria. In all cases, delivery using conjugation consistently showed the highest transposition efficiency compared to chemical transformation or electroporation. We determined the frequency of transposon insertions in all the species and proved the utility of the system by identifying genes involved in colony colouration in Shewanella oneidensis. The ease and the efficiency of the protocol developed here allow the creation of complete knock-out libraries in an extensive range of host microorganisms in less than a week with no requirement for preparatory modification.